2018
DOI: 10.1159/000488846
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ozone-Based Eye Drops: A Series of Cases in Veterinary and Human Spontaneous Ocular Pathologies

Abstract: Conjunctivitis, keratoconjunctivitis, and corneal ulcers are common eye disorders frequently diagnosed in both humans and animals, and are currently treated by topical administration of eye drops containing anti-inflammatory and antibacterial agents. The current molecules often lack efficacy because infections in hypoxic tissue contain methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa; thus, new products for the treatment of ocular pain and inflammation are needed. The use of ozone, a mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 9 publications
1
36
0
1
Order By: Relevance
“…Conjunctivitis, along with keratoconjunctivitis and corneal ulcers, is widespread not only in humans but also in animals (Spadea et al, 2018), as confirmed by our observations in Dnipro. Ophthalmic diseases are accompanied by similar clinical features (Giudici & Pressanti, 2014), so determining the etiological factors that may be represented by zoonotic pathogens plays an important role in the complex diagnosis and development of treatment interventions (Gerding et al, 1990).…”
Section: Discussionsupporting
confidence: 87%
“…Conjunctivitis, along with keratoconjunctivitis and corneal ulcers, is widespread not only in humans but also in animals (Spadea et al, 2018), as confirmed by our observations in Dnipro. Ophthalmic diseases are accompanied by similar clinical features (Giudici & Pressanti, 2014), so determining the etiological factors that may be represented by zoonotic pathogens plays an important role in the complex diagnosis and development of treatment interventions (Gerding et al, 1990).…”
Section: Discussionsupporting
confidence: 87%
“…This drawback has been overcome by developing a specific formulation for ophthalmic use, both in animals and humans, that is based on ozonated liposomal sunflower oil plus hypromellose (Ozodrop ® , FB Vision, Ascoli Piceno, Italy), which is well tolerated and biocompatible with the delicate tissue of the ocular surface. The most common eye disorders encountered in animals [76], such as conjunctivitis, keratitis, keratoconjunctivitis sicca, and corneal ulcers, share some symptoms with human conditions, such as redness, chemosis and exudation. These inflammatory anterior segment diseases necessitate adequate anti-inflammatory therapy.…”
Section: Topical Applications Of Ozonated Oilsmentioning
confidence: 99%
“…In fact, applying Ozodrop ® 3-4 times a day controls the pathology until recession. However, the topical administration of a collyrium (1-2 drops per eye every 4 h) needs to be more frequent and repeated to achieve clinical resolution and some patients suffer from a lack of compliance [76,77]. Furthermore, the ozone-based eye drops could be used as preparation for intraand extra-ocular surgical procedures (i.e.…”
Section: Topical Applications Of Ozonated Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gaseous ozone, as such, is highly unstable, but can be stabilised as ozonide, an organic form obtained by having gaseous ozone which reacts with the double bonds of the carbon atoms of plant oils: the derived ozonated oil retains the properties of ozone. To make it tolerated by the ocular surface, a nanoemulsion with ozonated oil within liposomes in solution with hypromellose and deionised water has been recently placed on the market in the form of eye drops [3,4].…”
Section: Introductionmentioning
confidence: 99%